Microstructure, tensile and electrical properties of gold-coated silver bonding wire. Issue 3 (February 2015) - Tseng, Yi-Wei; Hung, Fei-Yi; Lui, Truan-Sheng
Highlights: An Au-plated Ag wire is a new method to overcome reliability problems. The Au-coated layer can increase the oxidation resistance. A new test method, electrical tensile test, is proposed to confirm the wires. The Au-plated Ag wire is a robust and efficient scheme. Abstract: Au-coated Ag wire offers an oxidation-resistant layer and added benefits compared with pure Ag wires. It can remain unchanged without any deterioration for long storage periods under ambient atmospheric conditions and features superior bond strength. The surface characterization, electrical properties at high temperature, and electrical tensile properties of both pure Ag and Au-coated Ag wires are investigated for reliability assessment. The experiment confirmed that an Au layer on the surface of Ag wire can increase oxidation resistance and tensile strength. The experiment utilized a new test method, electrical tensile test, to confirm the performance of wires. The fractured surface from ductile to brittle fracture mode of the Au-coated Ag wire was caused by electromigration. Moreover, electrical test data can be considered as a reference in IC and LED packaging industries.